The ICP-MS Study on the Release of Toxic Trace Elements from the Non-Cereal Flour Matrixes After In Vitro Digestion and Metal Pollution Index Evaluation - Nekvapil, Jiří; Vilišová, Karolína; Petřík, Zdeněk; Yalçin, Erkan; Fišera, Miroslav; Gál, Robert; Salek, Richardos Nikolaos; Mrázková, Martina; Bučková, Martina; Sumczynski, Daniela (Foods (Basel, Switzerland), 2025)
Detailed research analysis of the contents of eight toxic trace elements in non-cereal flours was conducted using inductively coupled plasma mass spectrometry, and the release of elements from the flour matrixes after in vitro digestion was investigated. It also examines dietary intake and evaluates the metal pollution index. The highest digestibility value was measured with banana flour (92.6%), while grape seed flour was the least digestible, only 44%. The most abundant element was Al, followed by Ni, which was present (except banana flour) at concentrations of more than twice that found in food generally. The flax and milk thistle seed flours showed two orders of magnitude higher amounts of Cd than those measured in other flours. When consuming a 100 g portion of non-cereal flours, a consumer weighing 60 kg is exposed to the highest dietary exposures to Al and Ni (in the order of µg/kg bw); the exposures for the intake of Cd, Sn, Hg, As, Ag, and Pb are of the order of ng/kg bw. Grape seed flour was assessed as a significant contributor to the provisional tolerable weekly intake (PTWI) value of Al (16%); in addition, significant contributions of banana, pumpkin, grape, and milk thistle flours to the PTWI value of Hg, ranging from 15 to 22%, were determined. Furthermore, the contributions of milk thistle and flax seed flours to the provisional tolerable monthly intake (PTMI) value of Cd were also recognized as significant (specifically, 26 and 49%, respectively). The contributions of milk thistle, flax seed, and pumpkin seed flour to tolerable daily intake for Ni were estimated between 19 and 57%. The margin of exposure values for developmental neurotoxicity, nephrotoxicity, and cardiovascular effects obtained for the intake of Pb were considered safe. During the digestion process, the toxic elements that were the most retained in the matrices of grape and pumpkin seed flour were easily released from the banana flour. The retention factor, which was above 50% for Hg in the grape seed flour, was examined as the highest. All toxic trace elements, which were found to still be part of the undigested portion of the flours, could theoretically pass into the large intestine. In the future, more research is needed to clarify the possible carcinogenesis effect of toxic trace elements in the colon.
Keywords: milk thistle flour; pumpkin flour; grape seed flour; ICP-MS; metal pollution index; banana flour; toxic trace element; flax seed flour; in vitro digestibility